Goal Programming untuk Optimasi Jadwal Perkuliahan pada Fakultas Pertanian UNIMOR - Fried Markus Allung Blegur; Eva Binsasi (Saintek Lahan Kering, 2020)
The Faculty of Agriculture, University of Timor often has problems scheduling courses. Lectures in 7 study programs with 543 courses and 118 lecturers must be distributed into the 15 available rooms. This limitation causes lecture scheduling not to be evenly distributed for several lecturer. Some lecturers experience schedule buildup on certain days and time periods of the week. In addition, there is a fairly long time lag between one lecture and another on the same day for several lecturers. This scheduling problem is modeled using the Goal Programming method. The LINGO 11.0 software was used to solve this model. The results obtained are that each lecturer gets a lecture schedule that is evenly distributed on each day of the week without experiencing an overlap in lecture schedules. This model also solves the problem of the long time span between lecture schedules of several lecturers by limiting teaching breaks to only one time before starting the next lecture on the same day for each lecturer.